Investigation of Relation between Physiological Responses and Personality during Stress Recovery - Saha, Bitan; Becker, Linda; Garbas, Jens Uwe; Oppelt, Maximilian; Foltyn, Andreas; Hettenkofer, Sebastian; Lang, Nadine; Struck, Matthias; Rohleder, Nicolas; Mahesh, Bhargavi (2021 IEEE International Conference on Pervasive Computing and Communications Workshops and other Affiliated Events, PerCom Workshops 2021, 2021)
Stress is seen as an individual's reaction to external circumstances that are perceived as a threat. Reactions to stress are highly subjective in nature, depending upon numerous individualistic factors. The study of stress recovery and associated coping efforts can help mitigate adverse health effects. Therefore, understanding the interplay of psychological and physiological manifestations of stress in modeling the stress recovery patterns is of high importance. Previous studies have indicated an association between personality traits and physiological responses. However, definitive evidence for this association is lacking. This work attempts to investigate the correlation between personality traits, such as neuroticism and extraversion, and physiological responses such as electrocardiogram and salivary cortisol responses, to the Trier Social Stress Test. Gaussian mixture modeling technique is employed to automatically cluster individuals based on their personality traits and electrocardiogram responses. Simultaneously, individuals are classified based on changes in salivary cortisol levels. Resulting clusters are labelled based on the literature on stress recovery. The relationships between personality and physiology groups are investigated. Reduced stress recovery observed via salivary cortisol responses is associated with higher neuroticism and lower extraversion, as well as attenuated electrocardiogram recovery responses. Higher cortisol reactivity during stress is found to be positively associated with higher cortisol recovery. Therefore, the study implies that consideration of personality traits is likely to aid stress detection and recovery models.
CRIS-Team Scopus Importer:2021-06-18
Keywords: clustering; extraversion; Gaussian mixture model; heart rate variability; neuroticism; personality; Physiological stress recovery; salivary cortisol; Trier Social Stress Test